Interview with Lord Reed: KLR Editorial Board interviews - Akandwanaho, Jireh; Lennox, Amber (Kent Law Review, 2022)
Lord Reed Interview Transcript Jireh: Firstly, thank you for sitting down with us. How are you enjoying your time here at Kent Law School so far? Lord Reed: It’s a great pleasure to be here. I’ve been made very welcome by the staff and the students I’ve met, and I’ve met some very impressive young people doing lots of good work! Jireh: You have held various roles and different positions in your career, now leading to the Presidency of the Supreme Court; congratulations on that. How have you found the role so far, especially given the start of the pandemic soon after you were appointed, did it change anything for the role? Lord Reed: It’s always a challenge to lead an institution; especially one that’s as important and prominent as the Supreme Court. It would be a challenge at the best of times; the pandemic brought a whole set of challenges that I hadn’t anticipated. We had to adapt to working online, just like the University. We had the same sorts of problems of people not being able to come together and having to work from their homes; often without a quiet place to work, or with children still at home. Or people who live alone finding it depressing to be unable to go into work. We had a number of new judges join the court during the lockdown, some of whom had never met the other members of the court. The format of working online made hearings more constrained and formal than they would normally be. At the same time, the lockdown also prompted the introduction of changes, which I had in mind, faster than they would have otherwise happened. For example, instead of having enormous bundles of papers, having electronic files, with the documents for the cases being filed electronically. And having an electronic library, rather than using books. The court was able to cope with the pandemic very well, all things considered, but we are very pleased to be back in the building, having live hearings; as I’m sure you’re all happy to be back at university having live classes. Apart from the pandemic, it has been an interesting time for a number of reasons. One is that the government has had a variety of ideas for changes which could affect the courts. So we’ve had consultation papers to respond to, and discussions with government. Following the prorogation case, in particular, I was keen to try to build a stronger relationship with Parliament and ensure that our role was better understood than it may have been. And so I’ve been able to plan how best to go about that with the Speaker of the House of Commons, and the Speaker of the House of Lords. Although constraints on social gatherings have delayed going into that as fully as I’d have liked to. The opportunity will arise, probably next year. In the meantime we’ve taken steps to address a number of issues where I’ve felt the court could be doing more, for example, in relation to diversity and inclusion, and in relation to our international relationships with other courts around the world. Amber: In the past you’ve been the President of the EU Forum of Judges for the Environment; with COP26 having just ended, what is your view on agreements reached, and do you think we are doing enough to reach the goal of cutting emissions by 45% by 2030? Lord Reed: My impression is that we are probably not doing enough. I don’t mean we, personally, in the UK; my impression is that the UK is one of the countries doing more than the average. But I don’t think we are doing enough. The difficulty is that there are obviously all sorts of reasons why different countries are reluctant to do as much as they could, and we’ve no means of compelling them. I’m worried about the consequences in the long run. It really has to be a matter of diplomacy to persuade other people to do more than they seem currently willing to do. One can only hope that by the time they become prepared to do more, it isn’t too late for serious consequences to be averted. Amber: Do you think that there is a legal route that we might be able to take, to help the cause [climate crisis] along, so to speak? Lord Reed: Well, courts can help by enforcing environmental laws, obviously. Our Court, for example, has repeatedly made rulings requiring air pollution to be addressed, particularly in London, and that helps. But at the end of the day, in a democracy, courts apply the laws which the legislature approves, and the problem is more one to do with the state of public opinion. People watch a David Attenborough documentary, and they’re anxious about the fate of polar bears, but when it comes to the daily reality of their central heating, their cars, and all the other things which contribute to global warming, people are reluctant to make real changes unless they are compelled to do so. Jireh: Being an ad hoc judge on the European Court of Human Rights, do you feel that Brexit has affected your role in any way, and the connection between the British and the European Union judicial systems? Lord Reed: Well, our leaving the EU is obviously a profoundly important step, which will affect the law in many ways. One thing it won’t affect is the European Court of Human Rights, because that’s quite separate from the EU; I can continue to sit, if I am invited to, on the Strasbourg court. Also, it’s not affecting the relationship between judges in Britain and judges on the Continent. For example, I remain a associate member of the EU network of Presidents of Supreme Courts, by invitation; so I have regular meetings with the presidents of the 27 remaining member states’ Supreme Courts; we have a meeting with the French judiciary coming up at the end of this month [November], and we will be meeting the Irish and German judiciaries next year [2022]. The consequences for the law, of leaving he EU, haven’t yet really hit the courts. We haven’t yet had a case where we’ve had to consider EU retained law; so the consequences still lie ahead of us. Jireh: With the European Union relationship changing, do you feel like there will still be connections with the British judicial system, but just not as deep as before? Lord Reed: I think that’s probably true. It depends a lot on what the government’s strategy is going forward. They may want us to continue following a path which is aligned to that of the EU in some areas, I don’t know, but it is possible, for example, in the field of data protection. But there may well be areas of the law where they want to follow a quite different approach in the future, and the courts will go where domestic legislation leads them. Amber: It is evident that you’ve an interest in human rights and justice. The University of Kent, in partnership with the City of Canterbury, actually recently hosted a chapter of the Walk with Amal, to raise awareness for refugees. With your international legal experience, and understanding of human rights and justice, what is your view on the current refugee crisis, and how refugees are treated by human rights and by the legal systems? Lord Reed: I see the refugee crisis as something which is likely to be exacerbated by climate change, and I think it’s one of the most troubling aspects of modern life, which is likely to get much worse as life goes forward, as parts of the world which are currently inhabitable, become uninhabitable. The decent treatment of refugees is something which I regard as a moral imperative. I think we can be proud of how this country welcomed Jewish refugees in the Second World War and welcomed refugees from Uganda in the 1970s. Indeed we have a long history of welcoming refugees going back, for example, to the Huguenots who came over from France in the 17th century to escape religious persecution. Human Rights Law has an important part to play in the decent treatment of refugees, and it’s built into the legislation which governs asylum claims and immigration in the UK, and it’s the responsibility of the Courts to see that it’s properly applied. Amber: I’m actually in the Law, Literature and Film seminar group that I believe you’re going to be seeing later on. Lord Reed: Oh good! I enjoy films…and literature! Amber: We’ve just studied the Beekeeper of Aleppo, and there’s a process which all refugees go through where they’re not subject to any one legal system. Do you think there’s more that can be done, in terms of co-operation, between countries, in order to help with the refugee crisis? Lord Reed: I’m sure there is. It’s one of the unfortunate consequences of Brexit, that we lost the benefit of the Dublin convention. One sees at the moment on the Polish borders what can happen in the absence of international co-operation. I think the scale of the problem is such that you can’t reasonably expect countries to bear a disproportionate share of the burden, looking after those in need, because we’re talking about millions of people. It’s important that nations be prepared to share the burden, in order to ensure that there is a humanitarian response, rather than a tendency of each country to try to pass the problem onto its neighbour. Jireh: Do you think this is more the responsibility of the humanitarian organisations, given the issue’s global nature? Lord Reed: Humanitarian organisations have a very important role to play, but ultimately, the critical decisions are going to be made by national governments. It’s rather like climate change, that finding a solution at the level of an individual government is really not possible; so international co-operation between governments is the best way forward. But I say that as a member of the public, that’s nothing to do with my role as a judge. Amber: Finally, we wanted to thank you again for taking the time to sit down with us, we know you’re very, very busy. We would like to ask you: what parting words would you like to leave with the students of Kent Law School? Lord Reed: I think the most important thing, possibly, for any law student to understand is that, the law is not a series of incontestable propositions. Even if you open a text book, and you find a proposition supported by 10 authorities in the footnotes, you’re never going to be a successful lawyer and I think will have rather missed the point of studying law, if you would take that as a definitive answer. The law is very often contestable. When you read cases, and it’s important that you do read cases, you’ll often find that they either don’t support the proposition for which they’re cited, or it’s debateable that they do, or even if it’s clear that they do, they may have been decided at some time in the past when social life, and attitudes, were different from what they are now; there may be room for argument as to whether the same approach should still be followed, without modification, at the present time. This university is famous for an approach to the law which sets it in the context of society. Learning that lesson, you should always be aware that people create the law for their own time, and that precedents are there to be studied but, sometimes, departed from. Amber: What’s your highlight of your career where you felt you achieved that [departing from a precedent that needed to be departed from], either when you were a lawyer or when you were a judge, what’s your proudest moment? Lord Reed: One of the cases I heard when I was sitting on the European Court of Human Rights, was the case of Thompson and Venables, which was the case of the two boys convicted of killing James Bulger. It was obviously an appalling case, but the decision of the European Court established some important principles which had some profound consequences, not only for English law but for many legal systems. One of the most important of those was that there should be child appropriate ways of dealing with children in the justice system. So children of their age would nowadays be dealt with in a youth court rather than, as they were, in an ordinary adult crown court. There is also greater protection for children nowadays than there was at that time, such as from the psychological consequences that could follow from the treatment that they received. The other major change that the case brought about, was the ending of the role of politicians in criminal sentencing. At that time, the period to be served, by the boys, in custody, was fixed by the Home Secretary. As a result of the decision, it would now be fixed by the courts. That would now be taken for granted. It seems extraordinary now that a politician was deciding a criminal sentence. But that just shows how far we’ve come as a consequence of that judgment. Amber: Thank you so much Judge. Truly, thank you for your time.